Book-tax conformity: Empirical evidence from Germany - Benedikt Zinn; Christoph Spengel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
We use a unique matched tax return-financial statement data set to examine the magnitude and sources of book-tax differences in Germany. For the first time, the data set enables us to evaluate the extent to which financial and tax accounting differ in Germany in the most accurate manner. Despite the close link between financial and tax accounting in Germany, we find that corporate taxable income and income reported to shareholders diverge considerably. Regression results suggest that this reporting gap is largely attributable to legal differences between financial and tax accounting and we cannot provide evidence that tax aggressive reporting adds to it. However, further analyses show that firms actively engaged in corporate restructuring exhibit larger book-tax differences than other firms. We interpret this result as evidence of firms willing to give up the administrative advantages of a one-book accounting system in order to achieve desired tax or financial accounting result, if book-tax conformity is not required. Thus, the results not only provide insights into the relatively unexplored area of behavioral response to changes in the degree of book-tax conformity, but also add a new perspective to the discussion surrounding the implementation of the German Accounting Law Modernization Act (BilMoG) in 2010.
Keywords: H20; H25; M41; 330; book-tax conformity; book-tax differences; tax planning; Steuervermeidung; Bilanz; Steuerbilanz; Körperschaftsteuer; Steuerbemessung; Deutschland